Stylistic Analysis of Denny Caknan's Lyrics: Unveiling the Language of Indonesian Pop-Dangdut - Darnanda, Farhan; Waryanti, Endang; Sardjono, Sardjono (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2024)
This research analyzes the language style in Denny Caknan's song lyrics that are popular in Indonesia. By using physical poetry structure theory and stylistic theory, this research aims to identify and categorize the stylistic language used in Denny Caknan's song lyrics. The results show that Denny Caknan uses various styles of comparison, opposition, linking, and repetition to express his emotions. The most dominant language style is affirmation style, especially afferesis, which is often used to give a dramatic effect and strengthen the message in the lyrics. Using comparative language styles such as simile and metaphor enriches the meaning of the lyrics and provides emotional depth. In addition, oppositional language styles, such as hyperbole and irony, are used to express conflict and disappointment. Linking language styles such as metonymy and personification gives the lyrics an artistic and poetic feel. Repetitive language styles such as anaphora and epanalepsis create a distinctive rhythm and musicality. This research provides insight into the linguistic richness of Indonesian pop-dangdut and Denny Caknan's contribution to the genre, as well as highlighting his ability to string words together and convey feelings through music.